Influence of Surface Modification of Alumina on Improvement of Wetability in Aluminium Matrix Composite - Alireza Samiee; Mohammad Hosein Bina; Mahmood Meratian (Advances in Materials Science and Engineering)
In this research, aluminium powder (50 wt%) and alumina (50 wt%) were first milled at a specific ball-to-powder ratio in a high-energy planetary mill at different times to manufacture Al-Al2O3 composite. Then, the capsules of powdery composites (Al-Al2O3)CP produced at the milling stage were added to aluminium melt and cast through ex situ. Scanning electron microscope SEM was used to study the morphology of the capsules and the microstructure of the produced composite. The percentage of powdery composite capsules and reinforcing particles present in the microstructure of Al-Al2O3 composite was measured by Image Tool software. The results of the tests showed that, by optimizing the milling time to 5 hours, the alumina particles are sufficiently placed in the matrix of the capsules; on the other hand, alumina particles are also properly coated with aluminium powder. When these capsules are added to aluminium melt, the rate of the wetting of alumina particles greatly increases and accordingly the percentage of the reinforcing particles in the cast composite matrix increases dramatically. By surface modification and accordingly increasing percentage of Al2O3, the tensile strength increases and the tensile strength of the composites is higher than that of the matrix alloy.